Halal Traceability System and Halal Food Performance of SMEs Food and Beverage in Malaysia - Haslinda Hadis; Shahrizin Abd Sarhadat; Masran Tamin; Azaze Azizi Abdul Adis (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
Small and Medium Enterprise (SMEs) in food and beverage industry is one of the major sectors that contribute to Malaysia’s economic growth. The industry is a dynamic and growing sector that serves both the domestic Muslim population and the global market. An innovative halal traceability system is an integral to the halal food and beverage industry's growth and success. The innovation system contributes to improved production, quality control, transparency, increase consumer trust and compliance with halal standards. The adoption of halal traceability system among SMEs is crucial to improve the halal food and beverage industry performance. Hence, this study aims to investigate the impact of Technology Acceptance Model (TAM), entrepreneurship marketing dimension (EMD), and intention to adopt halal traceability system towards halal food performance among Malaysian food and beverage SMEs. The systematic random sampling will be employed in this study and self-administered questionnaire through both online and offline will be used to collect approximately 189 of potential respondents from East Malaysia (Sabah and Sarawak) and Peninsular Malaysia (Selangor and Kuala Lumpur). The expected result of this study will be useful to the importance growing of the halal traceability system in the food industry.